The Influence of Mudharabah, Musyarakah, Murabahah, Financing, Financing Risk, and Liquidity Risk on the Profitability of Private Sharia Commercial Banks - Vian Afri Liandi; Yuniorita Indah Handayani; Wiwik Fitria Ningsih (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
This research aims to determine the effect of mudharabah, musyarakah, murabahah financing, financing risk and liquidity risk on profitability in Private Sharia Commercial Banks in 2018-2022. The type of research used is quantitative research. The data used is secondary data through reports from each company. The population in this research is Private Sharia Commercial Banks registered with the Financial Services Authority (OJK). The data collection technique used was the purposive sampling method and obtained a sample of 9 companies. The data analysis methods used are classical assumption testing, multiple linear regression, coefficient of determination (R¬2) and hypothesis testing. The results show that musyarakah financing, murabahah financing and partial financing risk have a significant effect on profitability, while mudharabah financing and partial liquidity risk have no effect on profitability. Simultaneously mudharabah, musyarakah, murabahah financing, financing risk and liquidity risk influence profitability